Meningkatkan aktivitas belajar Bahasa Indonesia siswa sekolah dasar melalui joyful learning berbantuan Wordwall - Jannatul Afriani; M. Muzakki; Ibermarza Ibermarza (Universitas Pendidikan Indonesia, 2026)
The low level of student participation in the learning process necessitates implementing a fun learning model to improve it. This study aims to improve students' learning activity through the application of the Joyful Learning model, assisted by Wordwall media, in Indonesian language learning for fifth-grade students at SD Alam Muara Bungo. This study uses Classroom Action Research (CAR), conducted over two cycles in collaboration with the class teacher. Each cycle consists of planning, implementation, observation, and reflection stages. The study subjects were 22 fifth-grade students at SD Alam Muara Bungo. Data collection techniques included observation, documentation, and field notes. Data analysis was carried out descriptively, qualitatively, and quantitatively based on the results of observations of student learning activity. The results of the study indicate that the application of the Joyful Learning model, assisted by Wordwall media, improved students' learning activity from the active category in cycle I to the very active category in cycle II. Students became more enthusiastic about learning, more active in answering questions, more courageous in expressing opinions, and more focused during the activity. Thus, the use of the Joyful Learning model, supported by Wordwall media, can be a fun and effective alternative to increase learning activity among elementary school students, especially with abstract materials such as writing numbers and figures.